Detection of potentially novel paramyxovirus and coronavirus viral RNA in bats and rats in the Mekong Delta region of southern Viet Nam. (18th April 2017) - Berto, A.; Anh, P. H.; Carrique‐Mas, J. J.; Simmonds, P.; Van Cuong, N.; Tue, N. T.; Van Dung, N.; Woolhouse, M. E.; Smith, I.; Marsh, G. A.; Bryant, J. E.; Thwaites, G. E.; et al.
Summary: Bats and rodents are being increasingly recognized as reservoirs of emerging zoonotic viruses. Various studies have investigated bat viruses in tropical regions, but to date there are no data regarding viruses with zoonotic potential that circulate in bat and rat populations in Viet Nam. To address this paucity of data, we sampled three bat farms and three wet markets trading in rat meat in the Mekong Delta region of southern Viet Nam. Faecal and urine samples were screened for the presence of RNA from paramyxoviruses, coronaviruses and filoviruses. Paramyxovirus RNA was detected in 4 of 248 (1%) and 11 of 222 (4.9%) bat faecal and urine samples, respectively. Coronavirus RNA was detected in 55 of 248 (22%) of bat faecal samples; filovirus RNA was not detected in any of the bat samples. Further, coronavirus RNA was detected in 12 of 270 (4.4%) of rat faecal samples; all samples tested negative for paramyxovirus. Phylogenetic analysis revealed that the bat paramyxoviruses and bat and rat coronaviruses were related to viruses circulating in bat and rodent populations globally, but showed no cross‐species mixing of viruses between bat and rat populations within Viet Nam. Our study shows that potentially novel variants of paramyxoviruses and coronaviruses commonly circulate in bat and rat populations in Viet Nam. Further characterization of the viruses and additional human and animal surveillance is required to evaluate the likelihood of viral spillover and to assess whether these viruses pose a risk to human health.